2020
DOI: 10.1186/s12885-020-07539-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessing how health information needs of individuals with colorectal cancer are met across the care continuum: an international cross-sectional survey

Abstract: Background Studies evaluating health information needs in colorectal cancer (CRC) lack specificity in terms of study samples involving patients. We assessed how health information needs of individuals with CRC are met across the care continuum. Methods We administered an international, online based survey. Participants were eligible for the study if they: 1) were 18 years of age or older; 2) received a diagnosis of CRC; and 3) were a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 33 publications
1
20
0
2
Order By: Relevance
“…We invited females who are 18 years or older, have received a diagnosis of yCRC (before the age of 50 years), and are able to communicate in English. To recruit participants, we used the authors’ and their affiliated institutions’ social media channels (e.g., Twitter, Facebook, and Instagram) as well as drawing from a list of individuals who had participated in previous CRC-related research conducted by our research team and indicated their consent to be notified of future studies [ 18 , 19 , 20 , 21 ]. Individuals were directed to a study website, designed using Qualtrics, an online survey platform, which included information about the objective of the study, eligibility criteria, and what participation involves.…”
Section: Methodsmentioning
confidence: 99%
“…We invited females who are 18 years or older, have received a diagnosis of yCRC (before the age of 50 years), and are able to communicate in English. To recruit participants, we used the authors’ and their affiliated institutions’ social media channels (e.g., Twitter, Facebook, and Instagram) as well as drawing from a list of individuals who had participated in previous CRC-related research conducted by our research team and indicated their consent to be notified of future studies [ 18 , 19 , 20 , 21 ]. Individuals were directed to a study website, designed using Qualtrics, an online survey platform, which included information about the objective of the study, eligibility criteria, and what participation involves.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to caregivers, patients have more support needs during the treatment process, and CRC treatment-related information needs are met within the healthcare system. 43 Caregivers may have easier access to an internet self-help support group than patients that face challenges related to hospitalization, treatment, and adverse treatment effects. 10 Furthermore, they may lack the opportunity to actively find information in internet self-help support groups.…”
Section: Discussionmentioning
confidence: 99%
“…We know from Dau and colleagues’ survey work that patients with rectal cancer often have unmet psychosocial needs, specifically in the workplace, and concerning mental health, sexual function and nutrition/diet. 9 Additionally, Kang and colleagues found patients with rectal cancer are generally disappointed in commercially available patient education materials. 31 Coupled with the knowledge from this study, we recognise the need to develop educational tools and support for patients during rectal cancer treatment and survivorship.…”
Section: Discussionmentioning
confidence: 99%
“…One international survey explored-in binary fashion-whether patients felt their information needs were met in certain domains. 9 And a scoping review found most studies of colorectal cancer needs did not include patient perspective. 10 A comprehensive picture of patients' lived Strengths and limitations of this study ► Semistructured interviews performed with rectal cancer survivors about their lived experiences regarding their cancer care.…”
Section: Introductionmentioning
confidence: 99%